Investigating the Association Between Computer Game Addiction and Social Anxiety in Secondary School Students - KARACA, SEMRA (AVES PRESS LTD, 2016)
Objective: This study was conducted to investigate the association between computer game addiction and social anxiety levels in secondary school students. Methods: This study, which was descriptive and cross-sectional in design, was conducted in seven state secondary schools in Istanbul/Kadikoy. The data was collected using the participant information form, computer game addiction scale (CGAS) for children, and child social anxiety scale (CSAS), and the study was completed with 1019 students (556 males and 463 females). Results: Students were aged between 10 and 15 years, and the mean age was 12.85 +/- 1.16 years. Of all students, 54.6% were males and 45.4% were females. Majority (88.6%) of students had an internet connection at home, 98.3% were always playing online games, and 67.2% spent 0.5-3 h/day on the computer. The mean CGAS score was 43.27 +/- 16.31, and the mean CSAS score was 39.06 +/- 13.44. According to the mean CGAS score, 47.7% were normal computer users, 46.7% were problematic computer users, and 5.6% were computer game addicts. A moderately positive correlation was observed between the mean CSAS scores and CGAS total scores and subscale scores (r=0.24-0.31; p<0.01). Conclusion: According to the findings of this study, almost half of the students in the study sample group were problematic computer users. Social anxiety level was not high, and social anxiety was moderately correlated with computer game addiction.
Keywords: Student; computer game addiction; social anxiety